Electronic controlled CMOS inductor with patterned metal ground shields for fine inductance tuning application - Nur Syahadah Yusof; Norlaili Mohd Noh; Jagadheswaran Rajendran; Asrulnizam Abd Manaf; Shukri Korakkottil Kunhi Mohd; Yusman Mohd. Yusof; Harikrishnan Ramiah; Mohamed Fauzi Bin Packeer Mohamed (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper is on an inductance fine tuning technique which benefits from the idea of varying the number of metal plates of an inductor’s pattern ground shield (PGS) shorted to ground to change its magnetic fields. This technique is unique because the geometry and physical shape of the inductor remains untouched from its form in the process design kit (PDK) while the inductance is being tuned. The number of metal shields shorted to ground was controlled by an electronic circuit which consists of analog-to-digital converters and active switches. Both Sonnet EM simulator and Cadence Virtuoso were used for the inductor and circuit simulations. From the simulation, it was found that the inductance increased while the Q-factor decreased as more metal shields were shorted to ground. For instance, at 1.6 GHz, the simulated inductance was 8.8 nH when all metals were floated and 9.4 nH when all metals were shorted to ground. On the other hand, the simulated Q-factor was 10.4 when all metals were floated and 9.8 when all metals were shorted to ground. From both simulation and measured results, both inductance and inductance tuning range increased with frequency. From the measured results too, the inductance observed was 9.4 nH at 1.6 GHz, 10.8 nH at 2 GHz, and 13.5 nH at 2.5 GHz when all the metal shields were shorted to ground. The inductance tuning range was 6.2% at 1.6 GHz, 12.5% at 2 GHz, and 20% at 2.5 GHz. The measured results showed good correlation with the simulated results trend, but with smaller value of inductance, inductance tuning range and Q-factor.